Seasonal Variations in Ice-Front Position Controlled by Frontal Ablation at Glaciar Perito Moreno, the Southern Patagonia Icefield - Minowa, Masahiro; Sugiyama, Shin; Sakakibara, Daiki; Skvarca, Pedro (Frontiers in Earth Science, 2017)
The front position of calving glaciers is controlled by ice speed and frontal ablation which consists of the two processes of calving and subaqueous melting. However, the relative importance of these processes in frontal variation is difficult to assess and poorly understood, particularly for freshwater calving glaciers. To better understand the mechanism of seasonal variations involved in the ice front variations of freshwater calving glaciers, we measured front position, ice surface speed, air temperature, and proglacial lakewater temperature of Glaciar Perito Moreno in Patagonia. No substantial fluctuations in front position and ice speed occurred during the 15-year period studied (1999–2013), despite a warming trend in air temperature (0.059◦C a−1). Seasonal variations were observed both in the ice-front position (±50 m) and ice speed (±15%). The frontal ablation rate, computed from the frontal displacement rate and the ice speed, varied in a seasonal manner with an amplitude approximately five times greater than that in the ice speed. The frontal ablation correlated well with seasonal lakewater temperature variations (r = 0.96) rather than with air temperature (r = 0.86). Our findings indicate that the seasonal ice front variations of Glaciar Perito Moreno are primarily due to frontal ablation, which is controlled through subaqueous melting by the thermal conditions of the lake.